Determination of the optimal dose of ephedrine in the treatment of arterial hypotension due to general anesthesia in neonates and infants below 6 months old: the ephedrine study protocol for a randomized, open-label, controlled, dose escalation trial - A. S. Szostek; P. Boucher; F. Subtil; O. Zerzaihi; C. Saunier; M. de Queiroz Siqueira; F. Merquiol; P. Martin; M. Granier; A. Gerst; A. Lambert; T. Storme; et al. (Trials, 2021)
Abstract Background Arterial hypotension induced by general anesthesia is commonly identified as a risk factor of morbidity, especially neurological, after cardiac or noncardiac surgery in adults and children. Intraoperative hypotension is observed with sevoflurane anesthesia in children, in particular in neonates, infants younger than 6 months, and preterm babies. Ephedrine is commonly used to treat intraoperative hypotension. It is an attractive therapeutic, due to its dual action on receptors alpha and beta and its possible peripheral intravenous infusion. There are few data in the literature on the use of ephedrine in the context of pediatric anesthesia. The actual recommended dose of ephedrine (0.1 to 0.2 mg/Kg) frequently leads to a therapeutic failure in neonates and infants up to 6 months of age. The use of higher doses would probably lead to a better correction of hypotension in this population. The objective of our project is to determine the optimal dose of ephedrine for the treatment of hypotension after induction of general anesthesia with sevoflurane, in neonates and infants up to 6 months of age. Methods The ephedrine study is a prospective, randomized, open-label, controlled, dose-escalation trial. The dose escalation consists of 6 successive cohorts of 20 subjects. The doses studied are 0.6, 0.8, 1, 1.2, and 1.4 mg/kg. The dose chosen as the reference is 0.1 mg/kg, the actual recommended dose. Neonates and infants younger than 6 months, males and females, including preterm babies who undergo a surgery with general anesthesia inducted with sevoflurane were eligible. Parents of the subject were informed. Then, the subjects were randomized if presenting a decrease in mean blood pressure superior to 20% of their initial mean blood pressure (before induction of anesthesia), despite a vascular filling with sodium chloride 0.9%. The primary outcome is the success of the therapy defined as an mBP superior to 80% of the baseline mBP (prior to anesthesia) within 10 min post ephedrine administration. The subjects were followed-up for 3 days postanesthesia. Discussion This study is the first randomized, controlled trial intending to determine the optimal dose of ephedrine to treat hypotension in neonates and infants below 6 months old. Trial registration ClinicalTrials.gov NCT02384876 . Registered on March 2015.